Laser deposited superalloys with rotated substrate orientations: Microstructures and single-crystal formation. (1st January 2023) - Chen, W.J.; Han, S.X.; Guo, J.C.; Yang, R.N.; Lei, X.W.; Yao, W.J.; Wang, N.
Abstract: One- and multi-layer laser powder depositions were performed on single crystal (SX) Ni-based superalloy DD6 by rotating the substrate orientation around the [100], [010], and [001] crystallographic directions with the angle ξ [hkl] (hkl = 100, 010, 001) from the initial orientation (001)/[100], and the substrate orientation effect on the microstructure and SX nature were determined. It shows that for the one-layer deposition, the substrates with different rotation manners produce various dendritic domain distributions and stray grain (SG) susceptibilities in the deposited bead. Remarkably, one epitaxial dendrite domain can be only obtained for the [010]-axis rotation with ξ [010]  = ±45°, which can suppress the formation of SGs effectively. However, at least two dendrite domains exist for [100]- or [001]-axis rotations, leading to slight dependence of SG susceptibility on the orientation. The multi-layer deposition experiments reveal that the SX nature can be retained with ξ [010]  = 45°. The underlying mechanism of the orientation-dependent SG susceptibility is that different substrate orientations cause various columnar-to-equiaxed transition (CET) sensitivities. The difference in SG susceptibility between laser deposition and laser remelting is also discussed. Our results can provide an in-depth insight into controlling SG via substrate orientation in the laser processed SX superalloy. Graphical abstract: Image, graphical abstract